Health education for the elderly - Experience report - A. Klock (Scientific Electronic Archives, 2017)
The aging process has been widely discussed in recent years seen its steady population growth. Thus , new strategies are being coordinated to assist in the promotion, maintenance and recovery of health of this clientele .Among the actions it stands out health education, which has as objective to prepare individuals and / or groups to take control and responsibility over their own health, among others. This article aims to report the academic experience lived in a group of elderly , opposite the importance of health education actions.  The activities were held in 2015 with about 30 participants. To recruit them , they got help from the Community Health Agents, and the Church support by publicizing the meeting during the warnings of the masses. Several topics were discussed, including : Hypertension , Diabetes mellitus , Falls and Conscious and correct use of Oral Drugs. At the end of this experience it was possible to see how this population lacks information and how health education actions are needed to improve the knowledge and the elderly quality of life.